Retinal Manifestations During Severe Pre-Eclampsia / Eclampsia at Gabriel Toure Chu - Sidibe, Mohamed K; Gakou, Kalilou I; Nadio, Thierno; Ba, Kadiatou; Coulibaly, Brainima; Traore, Aly Badra; Bamani, Sanoussi (European Journal of Applied Sciences, 2026)
Introduction: Preeclampsia is a major public health concern. It is a systemic disorder that can affect multiple organs, including the eyes. The objective of this study was to assess retinal manifestations in severe preeclampsia/eclampsia in order to highlight the importance of ophthalmic monitoring in patients with this condition. Materials and Methods: We conducted a prospective study involving 342 patients diagnosed with preeclampsia or eclampsia, admitted between September 2022 and February 2023, over a 5-month period, in two university teaching hospitals in Bamako. Results: The mean age of the patients was 25.62 ± 7.062 years. Most of them (74.9%) had no prior history of arterial hypertension. In nearly 70% of cases, the pregnancies were not at term at the onset of preeclampsia or eclampsia. Blurred vision was the most frequently reported ophthalmic symptom. Retinal abnormalities were observed in 48.2% of right eyes and 47.1% of left eyes, including: 4 cases (2 OD, 2 OS) of serous retinal detachment; 2 cases (1 OD, 1 OS) of hypertensive choroidopathy; 1 case of left-eye branch retinal vein occlusion (BRVO) and 18 cases (10 OD, 8 OS) of grade III hypertensive retinopathy with optic disc edema. Discussion: The presence of retinal lesions appears to be a marker of severity in eclampsia, and their early detection enables prompt and appropriate management, thereby improving maternal and fetal outcomes. Conclusion: Fundus examination should be routinely included in the management of preeclampsia and eclampsia.